2019
DOI: 10.1186/s41983-019-0057-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for post-stroke depression in Sohag University Hospital

Abstract: Background: Depression is one of the important complications of stroke. Post-stroke depression is associated with more physical disability, especially in daily activities, poor functional outcome, and high mortality rate. Objective: Our study aimed to investigate the risk factors for development of post-stroke depression 3 months following stroke. Methods: This is a comparative study, comparing stroke patients with and without depression 3 months after the onset. Hamilton Depression Rating Scale (HDRS), Mini-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
5
1
1
Order By: Relevance
“…Further, the findings of this study reported that depression is significantly associated with stroke disability and functional dependence poststroke. This finding are in concurrence with the work which reported that PSD is significantly higher in stroke survivors reported higher disability[ 13 26 27 28 ] and functional dependence[ 26 29 ] in poststroke period.…”
Section: Discussionsupporting
confidence: 92%
“…Further, the findings of this study reported that depression is significantly associated with stroke disability and functional dependence poststroke. This finding are in concurrence with the work which reported that PSD is significantly higher in stroke survivors reported higher disability[ 13 26 27 28 ] and functional dependence[ 26 29 ] in poststroke period.…”
Section: Discussionsupporting
confidence: 92%
“…It was also stated by Mohammed et al, (2019) that hypertension, smoking habits, increased physical disability, and impaired cognitive function can cause (psychological) depression in stroke patients. Therefore it is necessary to manage various psychological problems (understanding of patients' adjustment and emotional problems can help them maximize rehabilitation, recovery, and community integration) which often cannot be simply treated through psychotropic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…http://ejournal.urindo.ac.id/index.php/kesehatan Adanya penyakit penyerta seperti diabetes mellitus menjadi faktor risiko terjadinya depresi pada mereka yang terkena stroke ditemukan secara signifikan dalam penelitian yang dilakukan oleh Kowalska, Katarzyna, et al (2020) (7). Mohammed, Gharib Fawi, et al (2019) dalam penelitiannya menemukan bahwa penyakit penyerta seperti hipertensi dan diabetes mellitus menjadi faktor risiko terjadinya depresi pada mereka yang terkena stroke (11).…”
Section: Pendahuluanunclassified